Sistem Pengurusan Sertifikat Konstruksi Kapal Pada KSOP Kelas II Marunda Oleh PT. Tirta Permai Bahari Cabang Tanjung Priok - Rajendra Sihite; Syarifur Ridho; Yefta Vianus Marbun (Jurnal Transformasi Bisnis Digital, 2026)
The maritime transport sector plays a vital role in international logistics, including the transport of special cargo such as live cattle, which requires specific administrative and operational handling. PT. Bahari Eka Nusantara Belawan Branch, as a ship agency company, is responsible for ensuring the smooth flow of ship services from arrival to departure at the Port of Belawan. This study aims to analyze the flow of agency management for special cattle cargo on the vessel MV Gloucester Express and to identify the coordination efforts carried out with relevant agencies to ensure service efficiency. The method used in this research is descriptive qualitative with data collected through field observations and literature studies. The results show that the agency flow involves three main stages: pre-arrival, arrival, and departure, with a focus on strict animal health documentation and coordination with the Quarantine Office. The study concludes that while the process generally runs well, administrative precision and real-time communication with the authorities are critical factors in preventing delays in unloading live cattle.